Experiential Learning at the Gatton Academy of Mathematics and Science in Kentucky. (October 2016) - Roberts, Julia Link; Breedlove, Lynette; Strode, Derick B.
This article describes the model for The Gatton Academy of Mathematics and Science in Kentucky where Kentucky's young people can extend their learning through university classes, global experiences, and research.